PERAN KOMUNITAS MEMBANGUN ETIKA KEGIATAN SOSIAL BERBAGI NASI DARI HATI DI KOTA BANDUNG - Danang Nugroho; Reza Kurnia putra; Ridho khoirian Nugraha; Muhammad Idris; Raihan Nur Fauzi; Reizan Khairul Siddiq; Rasyantha abdilah L O (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
The aim of this research is to find out how much the Bandung Sharing Rice community has contributed to increasing social awareness among Bandung City residents. Biddle and Thomas' role theory is cited in this research, which also uses qualitative descriptive techniques. Unstructured in-depth interviews are the method used in the data collection methodology. The stages of data reduction, data presentation, and drawing up conclusions are part of the data analysis process. By comparing data from different methodologies, triangulation procedures increase the validity of the data. The findings of this research show how members of the Nasi Bandung serving community raise social awareness by providing authentic examples through their actions and encourage others to do the same by asking for involvement on social media.